Somatic embryogenesis and plant regeneration of Capsicum baccatum L. - Peddaboina Venkataiah (Journal of Genetic Engineering and Biotechnology, 2016)
A plant regeneration protocol via somatic embryogenesis was achieved in cotyledon and leaf explants of Capsicum baccatum, when cultured on MS medium supplemented with various concentrations of 2,4-dichlorophenoxy acetic acid (2,4-D, 0.5–5.0 mg l−1) in combination with Kinetin (Kn, 0.5 mg l−1) and 3% sucrose. Various stages were observed during the development of somatic embryos, including globular, heart, and torpedo-stages. Torpedo stage embryos were separated from the explants and subcultured on medium supplemented with various concentrations of different plant growth regulators for maturation. Maximum percentage (55%) of somatic embryo germination and plantlet formation was found at 1.0 mg l−1 BA. Finally, about 68% of plantlets were successfully established under field conditions. The regenerated plants were morphologically normal, fertile and able to set viable seeds.